Non-infective subcutaneous emphysema of the hand: case report - Tejada Llacsa, Paul Jesús (2016)
Subcutaneous emphysema of noninfectious cause occurs rarely. We present this case due to the importance of discerning it from one with an infectious etiology. Our patient came to the hospital with increased volume in the left hand after suffering a cut on the fifth finger of that hand with a metal bar. Blood tests were within normal ranges. Signs of subcutaneous emphysema were noted in the hand X-ray. Empirical antibiotic therapy was initiated with improvement at 36 hours. This case is of interest to consider non-infectious causes in the differential diagnosis of hand emphysema.